Nitrogen fertilisation impacts greenhouse gas emissions, carbon footprint, and agronomic responses of beet intercropped with arugula - Cecílio Filho, Arthur Bernardes [UNESP]; Nascimento, Camila Seno [UNESP]; Pereira, Breno de Jesus [UNESP]; Nascimento, Carolina Seno [UNESP] (Elsevier, 2022)
Although the response of plants to nitrogen (N) in conventional systems has been extensively described in the literature, there is a lack of information available to refine the strategic N fertilisation program required in intercropping systems to match the nutrient supply with crop demands and reduce environmental impacts on greenhouse gas emissions. Therefore, this study aims to investigate the effect of N management on the growth, production, quality, greenhouse gas emissions (GHG) and carbon footprint of a beet-arugula intercropping system during two growing seasons (winter and summer). The efficiency of N fertilisation in each season was assessed by the supply of 20 N doses, varying the amounts applied at planting and as a side dressing (0–80, 0–120, 0–160, 0–200, 0–240, 20–80, 20–120, 20–160, 20–200, 20–240, 40–80, 40–120, 40–160, 40–200, 40–240, 60–80, 60–120,60–160, 60–200 and 60–240 kg N ha−1). GHG emissions and carbon footprint were calculated and converted to CO2 equivalent (CO2 eq) utilising IPCC methodology. The height, total and marketable productivities of beet plants were 33, 31 and 34% higher in winter than in summer, respectively. Arugula plants achieved the highest performance (height, fresh mass and yield) in summer. Considering the environmental impact on global warming/climate change caused by the use of N fertilisers, total GHG emissions may range from 1723.9 to 3369.8 kg CO2eq ha−1 cycle−1 according to the N dose applied. However, based on the carbon footprint, the application of 60–120 kg N ha−1 at planting and as side dressing was the best N dose, since it reduced the carbon footprint (equivalent to 0.134 g CO2eq kcal−1 vegetables) without compromising crop yield.
Keywords: Beta vulgaris; CO2 equivalent; Eruca sativa; Global warming; Intercropping system; Mineral nutrition